Two-year follow-up of a clustered randomised controlled trial of a multicomponent general practice intervention for people at risk of poor health outcomes - Richard L. Reed; Leigh Roeger; Billingsley Kaambwa (BMC, 2024)
Abstract Background This study was a two-year follow-up evaluation of health service use and the cost-effectiveness of a multicomponent general practice intervention targeted at people at high risk of poor health outcomes. Methods A two-year follow-up study of a clustered randomised controlled trial was conducted in South Australia during 2018-19, recruiting 1044 patients from three cohorts: children; adults (aged 18-64 years with two or more chronic diseases); and older adults (aged ≥ 65 years). Intervention group practices (n = 10) provided a multicomponent general practice intervention for 12 months. The intervention comprised patient enrolment to a preferred general practitioner (GP), access to longer GP appointments and timely general practice follow-up after episodes of hospital care. Health service outcomes included hospital use, specialist services and pharmaceuticals. The economic evaluation was based on quality-adjusted life years (QALYs) calculated from EuroQoL 5 dimensions, 5 level utility scores and used an A$50,000 per QALY gained threshold for determining cost-effectiveness. Results Over the two years, there were no statistically significant intervention effects for health service use. In the total sample, the mean total cost per patient was greater for the intervention than control group, but the number of QALYs gained in the intervention group was higher. The estimated incremental cost-effectiveness ratio (ICER) was A$18,211 per QALY gained, which is lower than the A$50,000 per QALY gained threshold used in Australia. However, the intervention's cost-effectiveness was shown to differ by cohort. For the adult cohort, the intervention was associated with higher costs and lower QALYs gained (vs the total cohort) and was not cost-effective. For the older adults cohort, the intervention was associated with lower costs (A$540 per patient), due primarily to lower hospital costs, and was more effective than usual care. Conclusions The positive cost-effectiveness results from the 24-month follow-up warrant replication in a study appropriately powered for outcomes such as hospital use, with an intervention period of at least two years, and targeted to older people at high risk of poor health outcomes.